Fishers and whales in Iceland: Details of whale interactions with fishing gear from the fishers’ perspective, with focus on humpback whales (Megaptera novaeangliae) - Basran, Charla J.; Rasmussen, Marianne H. (J. Cetacean Res. Manage., 2022)
In Iceland, as in many places globally, the detrimental impacts of whale interactions with fishing gear on both fisheries and whales are not well understood and managed. This study conducted anonymous questionnaires of Icelandic fishers and interviews of capelin purse seine boat captains to gather first-hand knowledge of the issues fishers face due to whale interaction with their fishing gear. Results suggest that the humpback whale is the large whale species that is most often entangled or encircled in fishing gear and causing damage, however on occasion other large whale species are interacting with gear as well. Interactions between humpback whales and fishing gear appears to be primarily concentrated in the north/northeast and southwest of the country where there is high fishing effort and known humpback whale feeding habitat. Humpback whale interactions with gear occurred most often with capelin purse seines, which are targeting humpback whale prey, and data suggests that bycatch of whales in this fishery may be underreported. Damage and losses due to whale collisions with gear were reported to cost fishers up to 55.000.000ISK, suggesting this can be a costly issue for which mitigation measures should be explored. The use of acoustic â€œpingersâ€ is one mitigation measure that has been previously tested by capelin purse-seiners and is something that captains indicated they would be interested in continuing to try. The creation of a whale entanglement/whale-gear interaction reporting system in Iceland would aid in gathering more data and quantifying how often these events are witnessed and what the consequences of these events are to both the fishers and the whales. This study provides new information about the consequences of large whale interactions with Icelandic fisheries and suggests that future collaboration with fishers can provide insight contributing to best management practices for sustainable fishing and whale conservation.